ESTUDO DO IMPACTO DO RUÍDO AERONÁUTICO NO ENTORNO DO AEROPORTO EURICO SALLES, VITÓRIA - ES - Fortes, Bárbara Carolina Soares; Amorim, Alexandre Cypreste (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Aeronautical noise and its impact on the health of the population exposed to it have been studied in different parts of the world. It is possible that the occupation of the surroundings of the Eurico Salles airport could generate several problems for the population that lives there. This article aims to carry out a study of the impact of aeronautical noise in the area of influence of the Eurico Salles Airport in Vitória, ES and to elaborate measures that can mitigate its impact. Methodological procedures were adopted to carry out a bibliographic review on the theme - noise, legislation on airport undertakings and possible damages to health. Measurements of sound pressure levels were made with the choice of points based on the location of the rails, current and under construction. The analysis of the results showed that, in fact, aeronautical noise in Vitória is above that recommended by NBR 10.151, NBR 10.152 and by WHO. However, this problem can be minimized by: a) limiting the airport's operating hours; b) change in the route of landings and departures; c) implementation of acoustic barriers; And finally, d) with the acoustic treatment of the buildings, so that there is isolation and consequently the improvement of the comfort.